Cartografias de ativismos em redes: feminismos periféricos e populares na imprensa digital (Brasil e Argentina/ 2013 -2018) - Quintino, Marilene Rodrigues (2026)
This thesis analyzes how the relationships between gender, politics, and communication have become a central axis in the political and sociocultural transformations that occurred in Brazil and Argentina between 2013 and 2018. Situated in the context of the intense reconfigurations of activist dynamics that marked the beginning of the 21st century, a dual movement characterizing the period is observed: the reorganization of feminisms and the emergence of digital communication closely linked to these processes. It examines how the connections and distances between these processes in these Southern Cone countries highlight both their national specificities and transnational dynamics of social mobilization and narrative disputes. In this context, on one hand, it seeks to understand how the so-called Feminist Spring — or Fourth Wave — dialogued, strained, and guided new arrangements of activism throughout the progressive cycle of the Pink Tide, as well as repositioned itself in the face of the subsequent conservative shift in the region. On the other hand, it investigates the emergence of the so-called digital feminist press, an analytical category formulated to reflect on a set of communication initiatives that have been established as spaces for critical storytelling, symbolic dispute, and the creation of new repertoires of collective action both within and outside the digital environment. The research undertakes a mapping of network concepts and collaborative practices that structure the production of meanings and the formulation of political strategies in digital media and on the streets. To this end, it analyzes the discourses produced by the portals Nós, Mulheres da Periferia, LatFem, Marcha, and the magazine Amazonas, understood as counter-hegemonic communication experiences in which plural forms of elaborating these new feminisms were articulated in light of identity frameworks, culture, and historical references that continuously dialogued with the present and the past, as well as with local and regional dynamics in the Latin American context. By examining their editorial practices, languages, and narrative repertoires, the investigation explores how these digital initiatives established new forms of mediation in the public sphere, focusing especially on the agendas of a young generation of activists – among them Black, Indigenous, and LGBTQI+ women – who, within the scope of this research, shape the so-called popular and peripheral feminisms to discuss the mediations and intersections between social mobility, gender, and race in these countries. It is supported, as a basic hypothesis, that this digital feminist press exerted significant influence on the political and symbolic field of contemporary feminisms that escape dichotomous interpretations, establishing itself as a locus of meaning production and collective imagination in the face of the radical transformations and inflections that marked the decade